Faktor-Faktor yang Memengaruhi Volatilitas Harga Beras Masa Pandemi Covid-19 di Indonesia - jojo, Jojo; Feriansyah, Feriansyah; Frasipa, Ana (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
Rice is one of the strategic food commodities in Indonesia. Unbalanced demand and supply of food can cause economic and social turmoil. Covid-19 has disrupted the world's food system with the closure of a number of regions and the distribution and movement of the food trade chain is hampered. The Covid-19 pandemic has not only damaged health but also had an impact on economic stability. This study aims to analyze the factors that influence the volatility of Indonesian rice prices before and during the Covid-19 pandemic. The data used uses monthly time-series secondary data. Starting from January 2010 to February 2021. The Vector Error Correction Model (VECM) method was used in this study. The results showed that the factors that influence the volatility of Indonesian rice prices in the long term are world oil prices, rice production, world rice prices and the rupiah exchange rate. Meanwhile, in the short term, it is changes in rice price volatility in the previous period, changes in rice prices, changes in world oil prices, changes in exchange rates and the Covid-19 pandemic.